Visual Assessment of Aqueous Humor Outflow. Issue 2 (March 2019) - Xie, Xiaobin; Akiyama, Goichi; Bogarin, Thania; Saraswathy, Sindhu; Huang, Alex S.
Abstract : Abstract: : In the past decade, many new pharmacological and surgical treatments have become available to lower intraocular pressure (IOP) for glaucoma. The majority of these options have targeted improving aqueous humor outflow (AHO). At the same time, in addition to new treatments, research advances in AHO assessment have led to the development of new tools to structurally assess AHO pathways and to visualize where aqueous is flowing in the eye. These new imaging modalities have uncovered novel AHO observations that challenge traditional AHO concepts. New behaviors including segmental, pulsatile, and dynamic AHO may have relevance to the disease and the level of therapeutic response for IOP‐lowering treatments. By better understanding the regulation of segmental, pulsatile, and dynamic AHO, it may be possible to find new and innovative treatments for glaucoma aiming at these new AHO behaviors.